Surface modification of small intestine submucosa in tissue engineering. Issue 4 (18th May 2020) - Zhao, Pan; Li, Xiang; Fang, Qin; Wang, Fanglin; Ao, Qiang; Wang, Xiaohong; Tian, Xiaohong; Tong, Hao; Bai, Shuling; Fan, Jun
Abstract: With the development of tissue engineering, the required biomaterials need to have the ability to promote cell adhesion and proliferation in vitro and in vivo . Especially, surface modification of the scaffold material has a great influence on biocompatibility and functionality of materials. The small intestine submucosa (SIS) is an extracellular matrix isolated from the submucosal layer of porcine jejunum, which has good tissue mechanical properties and regenerative activity, and is suitable for cell adhesion, proliferation and differentiation. In recent years, SIS is widely used in different areas of tissue reconstruction, such as blood vessels, bone, cartilage, bladder and ureter, etc. This paper discusses the main methods for surface modification of SIS to improve and optimize the performance of SIS bioscaffolds, including functional group bonding, protein adsorption, mineral coating, topography and formatting modification and drug combination. In addition, the reasonable combination of these methods also offers great improvement on SIS surface modification. This article makes a shallow review of the surface modification of SIS and its application in tissue engineering.